The Effects of Non-Cash Payment Instruments on Money Supply (M2) in Indonesia In The 2019-2024 Period - Nindrianto, Nabila Rahma; Galuh, Ajeng Kartika (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2025)
This study identifies a research gap regarding the impact of non-cash payment tools on money circulation (M2) in Indonesia, especially in relation to the context of rapid development of financial technology and evolving societal behavior in making transactions. This study seeks to examine the measurable influence of ATM/debit cards, credit cards, and electronic banking variables using control variables on money circulation (M2) during the period 2019-2024. This research method applies a quantitative approach with an explanatory design, using secondary data obtained from official reports published by Bank Indonesia and the Central Statistics Agency are tested using multiple linear regression to examine the causal relationship between output variables and input variables. The results of this analysis reveal that the volume of ATM/debit card transactions has an insignificant impact with a positive direction. While credit cards and e-banking have a significant impact with a negative and positive direction respectively related to money circulation (M2) in Indonesia. As well as inflation and interest rates have an insignificant impact with a positive and negative direction respectively related to money circulation (M2) in Indonesia. Keywords: Money Supply, Non Cash Payment, Electronic Banking